The Social and Lingual-Cultural Aspects of a Language - Khushmurodova Shakhnoza Shaymonkulovna (Zien Journals, 2021)
This article is about the language which represents social and cultural aspects that helps define the specifics of the language as a systematic- structural unity. A language is a unique and complicated formation because it can be investigated from different points of view. Social side of a language studies specific means of representatives of definite social or ethnic groups.
Keywords: Social; cultural; speech formation; Sociolinguistics